A cognitive–existential intervention to improve existential and global quality of life in cancer patients: A pilot study. Issue 4 (22nd July 2014) - Gagnon, Pierre; Fillion, Lise; Robitaille, Marie-Anik; Girard, Michèle; Tardif, François; Cochrane, Jean-Philippe; Le Moignan Moreau, Joanie; Breitbart, William
Abstract Objective: We developed a specific cognitive–existential intervention to improve existential distress in nonmetastatic cancer patients. The present study reports the feasibility of implementing and evaluating this intervention, which involved 12 weekly sessions in both individual and group formats, and explores the efficacy of the intervention on existential and global quality of life (QoL) measures. Method: Some 33 nonmetastatic cancer patients were randomized between the group intervention, the individual intervention, and the usual condition of care. Evaluation of the intervention on the existential and global QoL of patients was performed using the existential well-being subscale and the global scale of the McGill Quality of Life (MQoL) Questionnaire. Results: All participants agreed that their participation in the program helped them deal with their illness and their personal life. Some 88.9% of participants agreed that this program should be proposed for all cancer patients, and 94.5% agreed that this intervention helped them to reflect on the meaning of their life. At post-intervention, both existential and psychological QoL improved in the group intervention versus usual care (p = 0.086 and 0.077, respectively). At the three-month follow-up, global and psychological QoL improved in the individual intervention versus usual care (p = 0.056 and 0.047, respectively). Significance of results: This pilot study confirms the relevance of the intervention and the feasibility of the recruitment and randomization processes. The data strongly suggest a potential efficacy of the intervention for existential and global quality of life, which will have to be confirmed in a larger study.